Sofrimento psíquico e acolhimento de adolescentes na prática dos psicólogos da atenção básica em saúde - Cardoso, Yasmim Oliveira (Universidade Federal do Tocantins, 2025)
The WHO defines adolescence as the period between the ages of ten and nineteen, marked by vast transformations that are important for human development. Historically, there have been various attempts to explain or control the adolescent subject, some of which have been quite stigmatized based on the concept of the adolescent as a problem subject or a subject to be controlled by the state and its institutions. Given the advances made in brazilian legislation and the approval of the ECA, adolescents were granted the status of subjects of rights and, therefore, should have access to all basic rights such as education, food, housing, protection and health. In the latter, a demand that has been growing especially since 2011 is linked to the mental health of this population, which has shown increasing rates of psychological suffering, not only related to diagnosed disorders, but also to suicide. With this in mind, the general aim of this study is to investigate what the scientific literature has produced on the work processes of psychologists in Primary Care, from the perspective of the expanded clinic, in welcoming adolescents in psychological distress, as well as to find out about the practices adopted and the understandings of adolescence used by professionals. The methodology used was an Integrative Literature Review, with data collected from the Scielo and Index-Psychology databases. After the pre-selection of articles, a total of 12 articles were analyzed in the final stage and the results showed that, although progress has been made in the area and there are already health policies that can cover this public, there are still several problems that affect work with adolescents, such as: the stereotyped view of adolescence, the high rate of referrals from basic services to specialized services, the difficulty of carrying out intersectoral work, the low number of psychology professionals in PHC, the lack of matrix support and the dismantling of the NASF.